Avaliação do potencial antibacteriano dos óleos essenciais de Lippia origanoides e Piper divaricatum - CASTRO, Stella Martins (2022)
It is believed that Brazil, for containing a vast diversity of plant species, has great potential in the prospecting of assets with pharmacological activity and medicinal applicability. Among the species that stand out with biological activity are Lippia origanoides and Piper divaricatum that present molecules in the composition of essential oils with antibacterial properties. This paper aims to investigate the antibacterial activity of the essential oils from Lippia origanoides and Piper divaricatum species against Escherichia coli, Staphylococcus aureus, Enterobacter aerogenes, Klebsiella pneumoniae, Pseudomonas aeruginosa and Enterococcus faecalis bacteria, through Disc-diffusion and Minimum Inhibitory Concentration tests. A great antimicrobial potential was identified in these oils, favorable to the development of new broad-spectrum drugs that can provide a lower degree of toxicity and more efficiency.